Liver Involvement in Acute Respiratory Infections in Children and Adolescents – Results of a Non-interventional Study - Kamin, Wolfgang; Adams, Ortwin; Kardos, Peter; Matthys, Heinrich; Meister, Norbert; Strassburg, Christian P. (Frontiers in Pediatrics, 2022)
Background: In children and adults with acute respiratory tract infections (ARTI), elevations of serum liver enzyme activities are frequently observed in clinical practice. However, epidemiological data particularly in the pediatric population are very limited. The aim of this study was to assess the incidence of hepatic involvement, to identify the viruses and to analyze risk factors in children and adolescents with ARTI in a real-world setting. Methods: We report on a prospective, multicenter, non-interventional study with 1,010 consecutive patients aged 1 to 17 years with ARTI who consulted a physician within 5 days after onset of symptoms. Laboratory blood tests and PCR virus detection in nasopharyngeal lavage were performed at first presentation and after 3–7 days. Patients with elevated activities of serum liver enzymes (ASAT, ALAT and γ-GT) were determined in local laboratories and values were normalized by dividing by the individual upper limit of the normal range (ULN). The resulting index (<1 means below ULN, >1 means above ULN) allowed to compare results from laboratories with different reference ranges. Results: Laboratory test results of 987 patients were available at first visit. 11.1% (95% CI: 9.2–13.3%) exhibited an elevation of ASAT, ALAT, and/or γ-GT activities. Virus DNA or RNA was identified in nasopharyngeal lavages of 63% of the patients. 12.2% of patients with positive PCR and 9.7% of those with negative PCR (p=0.25) had elevated serum liver enzyme activities. The highest rates were observed in patients with a positive result for influenza B virus (24.4%) followed by human metapneumovirus (14.6%), and human coronavirus (others than SARS-CoV-2) (13.6%). The rate of children and adolescents with ARTI and elevation of serum liver enzyme activities correlated with the virus species and with overweight of the patients but did not differ in patients with or without previous medication intake. Conclusions: Elevated enzyme activities are present in about 10% of children and adolescents with ARTI. In our cohort, these elevations were mild to moderate; probably resulting from an inflammation process with hepatic involvement.